Care-Seeking Behavior After Notification Among Young Women With Recurrent Sexually Transmitted Infections After Pelvic Inflammatory Disease. (October 2016) - Butz, Arlene M.; Gaydos, Charlotte; Chung, Shang-En; Johnson, Betty H.; Huettner, Steven; Trent, Maria
Objective . To determine the level of nurse case management and outreach required to notify young women with sexually transmitted infection (STI) positive test results after pelvic inflammatory disease (PID) and percent seeking treatment. Methods. Participants (N = 153) were enrolled in a clinical trial of young women diagnosed with PID and followed for 3 months for recurrent STIs. Vaginal swabs were obtained at 1 and 3 months. All participants were notified of positive STIs at 1 and 3 months and treatment arranged. Data were analyzed with logistic regression for comparison of treatment status by number of nurse contacts. Results . Over the 3-month period, 59 participants (38.6%) tested positive for one or more STIs and all received notification. Only 50% (19/38) of participants with STI at 1 month and 43% (16/37) at 3 months received treatment. Conclusions . Despite the high notification rate of positive test results for young adults with recurrent STIs, many failed to seek treatment.